Comparison on cognitive performance among schoolchildren born prematurely according to the presence of intracranial hemorrhage in the neonatal period - Marcia Salim de Martino; Leandro Lopes Fernandes Alves; Cristina Ortiz Sobrinho; Adauto Dutra Moraes Barbosa
Abstract Objectives: to compare the cognitive performance of schoolchildren born prematurely according to the presence of intracranial hemorrhage (ICH) during the neonatal period. Methods: a cross-sectional cohort study of schoolchildren between the ages of 6-8 years old, born prematurely with or without a history of neonatal ICH. Between January and December 2015, some children were followed up at the outpatient clinic of a tertiary hospital and underwent a cognitive evaluation by using the Wechsler Intelligence Scale for Children, Third Edition (WISC-III) and they were divided into two groups: those with no history of ICH (control group) and those with ICH (case group), confirmed by a transfontanelar ultrasound in the prenatal period. Results: 39 schoolchildren were included, 21 cases and 18 controls. There was no difference in gestational age or chronological age at evaluation between the groups. Also there was no significant difference in subtest scores between the groups. Conclusions: WISC-III evaluated the cognitive performance in children, born preterm, aged 6-8 years old, and had neonatal ICH did not differ from those of their peers without a history of ICH. These findings suggest that, in preterm infants, a neonatal diagnosis of ICH may not be associated with cognitive performance at school age and this should be investigated through a longitudinal study.